ChemInform Abstract: Reductive Cross‐Coupling of Nonaromatic, Heterocyclic Bromides with Aryl and Heteroaryl Bromides. Issue 50 (16th December 2014) - Molander, Gary A.; Traister, Kaitlin M.; O'Neill, Brian T.
Abstract The present reaction allows the direct C—C bond formation between two organic halides without the use of organometallic reagents.